Australian Marsh Beetles (Coleoptera: Scirtidae). 7. Genus Nothocyphon, new genus - Zwick, Peter (Zootaxa, 2015)
The new genus Nothocyphon (type species: Helodes (Cyphon ?) lindensis Blackburn, 1892) is proposed for small Contacyphon-like Australian beetles. The included species exhibit a generalized body structure, lacking the derived character expressions of related genera. Male tergite 9 is very weakly developed, membranous and bare. This is derived but as a reduction only weakly supports the monophyly of Nothocyphon.The new genus includes 39 species, with 37 newly described herein: Nothocyphon alces, n. sp., N. amita, n. sp., N. amphora, n. sp., N. armatus, n. sp., N. armstrongi, n. sp., N. auritus, n. sp., N. banksiae, n. sp., N. biserratus, n. sp., N. brevihamatus, n. sp., N. crux, n. sp., N. denticulatus, n. sp., N. donnabuangi, n. sp., N. esau, n. sp., N. frater (Blackburn), n. comb., N. horridus, n. sp., N. ímitator, n. sp., N. isolaeregis, n. sp., N. lanceolatus, n. sp., N. lindensis (Blackburn), n. comb., N. multidentatus, n. sp., N. naso, n. sp., N. nungatta, n. sp., N. pacificus, n. sp., N. patruelis, n. sp., N. platyphallus, n. sp., N. plicatus, n. sp., N. radula, n. sp., N. sarcophilus, n. sp., N. scutiger, n. sp., N. serratipenis, n. sp., N. signatus, n. sp., N. soror, n. sp., N. taeniatus, n. sp., N. taurus, n. sp., N. thylacinus, n. sp., N. triangulum, n. sp., N. vandiemeni, n. sp., N. wattsi, n. sp., N. ypsilon, n. sp.Lectotypes are designated for N. frater (Blackburn) and N. lindensis (Blackburn). All species are redescribed or described, and illustrated. Several informal species groups are recognized, and identification keys to males are provided.